Optimization by factorial analysis of caprylic acid precipitation of non-immunoglobulins from hiperimmune equine plasma for antivenom preparation - Nudel, Berta Clara (2012)
Optimization of caprylic acid precipitation of equine plasma non-immunoglobulin proteins for antivenom preparation was achieved by regression analysis of the responses of three highly significant factors assayed by factorial design. The factors studied were caprylic acid concentration, plasma pH and temperature, and their response was assessed in terms of filtration speed, residual albumin, total protein content and turbidity. The results evidenced that the three variables are involved in the precipitation process. Moreover, the factors displayed significant interactions, indicating that their levels distinctly affect the optimization procedure. The best combination was 3% caprylic acid, 37 °C and plasma pH 4.9; under these conditions, all immunoglobulins and only 0.1% albumin remained in the supernatant, in a very fast and simple procedure. After formulation, the antivenom obtained by this procedure presented full lethality neutralizing activity and absence of protein aggregates.